Argumentation Through Languages and Cultures - Plantin, Christian (Cham : Springer Nature Switzerland : Imprint: Springer, 2022)
This book examines argumentative situations as they develop in different cultures and language groups. It considers the development of argumentation studies, making greater allowance for the specificities of argument as developed by "non-mainstream cultures"; the contribution of Jainism to the framework of philosophical disputation in India; duel songs as an institutionalized argumentative genre practiced by Ammassalik culture within the Inuit community; the application of the Muslim theological-legal reasoning system to evaluate two traditional, pre-Muslim traditional practices in Borneo; the annotation of schemes on the basis of Walton's taxonomy of argument schemes and Wagemans' Periodic Table of Arguments; methodology proposed for the reconstruction and analysis of "double-mode" arguments in advertisements, combining the instruments developed in social semiotics, pragmatics, and argumentation theory; and a review of the argumentation-theoretical literature on metaphor in argumentative discourse. This book is of interest to students and researchers in argumentation studies, rhetoric, philosophy, cultural studies and language studies. Previously published as a Special Issue in the journal: Argumentation "Special Issue Title: Argumentation through languages and cultures" Chapters "Annotating Argument Schemes" and "The Study of Metaphor in Argumentation Theory" are available open access under a Creative Commons Attribution 4.0 International License via link.springer.com.
Argumentation Through Languages and Cultures -- Jain Philosophers in the Debating Hall of Classical India -- Attack, Defense and Counter-Attack in the Inuit Duel Songs of Ammassalik -- Arsyad Al-Banjari's Dialectical Model for Integrating Indonesian Traditional Uses into Islamic Law -- Annotating Argument Schemes -- Reconstructing Multimodal Arguments in Advertisements: Combining Pragmatics and Argumentation Theory -- The Study of Metaphor in Argumentation Theory.
Keywords: Culture-Study and teaching; Philosophy; Language and languages-Style.; Rhetoric; Pragmatics; Linguistics; Cultural Studies; Philosophy; Rhetorics; Pragmatics; Linguistics